2001
DOI: 10.1097/00002371-200107000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Topical Transforming Growth Factor-β3 in the Prevention or Alleviation of Chemotherapy-Induced Oral Mucositis in Patients with Lymphomas or Solid Tumors

Abstract: Transforming growth factor (TGF)-beta3 has been hypothesized to prevent or alleviate oral mucositis (OM) in cancer patients receiving high-dose chemotherapy (CT). Two double-blind, placebo-controlled, multicenter, phase II studies of TGF-beta3 were initiated in the United States, Europe, and Argentina in patients with lymphomas or solid tumors who were receiving highly stomatotoxic CT regimens. Patients were to apply 10-mL mouthwash applications of TGF-beta3 (25 microg/mL) or placebo four times daily (or twice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…TGF-β mouthwashes or enriched food were not effective to reduce oral mucositis in the used formulations [80][81][82]. A mouthwash with bovine milk-derived whey growth factors (PV-701) was well tolerated, and as compared to historical controls, the severity as well as the duration of oral mucositis seemed to be decreased in autologous HSCT recipients [83].…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 99%
“…TGF-β mouthwashes or enriched food were not effective to reduce oral mucositis in the used formulations [80][81][82]. A mouthwash with bovine milk-derived whey growth factors (PV-701) was well tolerated, and as compared to historical controls, the severity as well as the duration of oral mucositis seemed to be decreased in autologous HSCT recipients [83].…”
Section: Granulocyte Colony-stimulating Factormentioning
confidence: 99%
“…Topical application of TGF-␤3 prior to chemotherapy with 5-Fluorouracil in hamsters resulted in a significant reduction in oral mucositis (Sonis et al, 1997). Despite these early encouraging results, however, a doubleblind, placebo-controlled, multi-center phase II clinical trial has shown that TGF-␤3 is not effective in the prevention or alleviation of chemotherapy-induced oral mucositis (Foncuberta et al, 2001). In chronic wounds, high levels of proteases causing cytokine breakdown, the presence of underlying systemic disease, and the lack of vascularity at the wound site, together with the placebo effect of any clinical trial, could contribute to these clinical findings.…”
Section: (D) Wound Healingmentioning
confidence: 99%
“…68,69 In a hamster model of chemotherapy-induced oral mucositis, application of TGF-β3 reduces the severity and duration of the resulting mucositis, 70 and clinical trials of TGF-β3 to treat this condition are underway. 71 TGF-β has also been shown to accelerate the repair of bone defects. In canine models, both TGF-β1 and TGF-β2 have been effective in increasing bone formation when applied to defects in the alveolar ridge and in the humerus, respectively.…”
Section: Possible Use Of Tgf-β Ligands For Therapeutic Interventionmentioning
confidence: 99%
“…109 This proteolytic degradation of ligand may have contributed to the inefficacy of topical TGF-β3 in treating chemotherapy-induced oral mucositis in patients with lymphomas and solid tumors. 71 In spite of these problems, some current clinical modalities may be acting by decreasing TGF-β signaling. The success of angiotensin-converting-enzyme inhibitors in treating diabetic nephropathy, interferon-α in treating hepatic fibrosis, azathioprine and prednisone in treating autoimmune hepatitis, and interferon-γ in treating pulmonary fibrosis is due, in part, to the ability of these agents to reduce serum levels of TGF-β.…”
Section: Therapeutic Applications: Problems and Perspectivesmentioning
confidence: 99%